Management of diabetic cardiomyopathy: the implications for low resource settings - T. A., Azeez,; Durotoluwa,. I. M.,; Oluwasanjo O. O., (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Cardiovascular diseases are the commonest cause of mortality in people living with diabetes mellitus. Prominent among the various cardiovascular diseases complicating diabetes is diabetic cardiomyopathy. It is characterized by cardiac dysfunction in a patient with diabetes having excluded other causes of cardiac dysfunction such as coronary heart disease, hypertensive heart disease and valvular heat disease.Diabetic cardiomyopathy has chronic hyperglycemia as the central theme of its pathophysiology. In the early phase, it is asymptomatic. In the late phase, it presents with heart failure. The diagnostic investigation of choice is echocardiography. Treatment is aimed at optimizing glucose control and using cardioprotective medications such as GLP-1 agonists and SGLT-2 inhibitors.Managing the disease has myriads of implications for low resource settings. Prevalence of diabetes is increasing at higher rate in these nations and it is expected that the incidence of diabetic cardiomyopathy will rise faster in these regions. More researches need to be focused in this direction as the data from low resource settings about diabetic cardiomyopathy is very scanty. The availability of the diagnostic tools in low resource settings is inadequate and this may delay diagnosis. Also, drugs like sulphonylureas and thiazolidinediones which are cheap and readily available but which may increase the chance of heart failure are still commonly used in low resource settings. Cardioprotective medications such as GLP-1 agonists are unaffordable and not readily available in low resource settings.This review aims to highlight the implications of managing diabetic cardiomyopathy in low resource settings so as to divert more attention to the disease, in terms of research and policies. These will help to alleviate the burden of diabetic cardiomyopathy in low resource settings.